ACTIVITIES IN TEACHING ENGLISH VOCABULARY FOR YOUNG LEARNERS IN FIVE KINDERGARTENS IN INDRAMAYU - Natalia Anggrarini (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2018)
Childhood Education essentially aims at providing stimulation in all aspects of child development especially in language development. This study is attempted to investigate activities in teaching English vocabulary to young learners. To provide good education in early childhood the teacher has to understand their characteristics and know their needs according to their developmental level. In accordance with the world of early childhood, children learn through play (learning through play) and interesting learning process for them (playing is learning).Thus, the teacher needs to provide activities that meet the students needs and present them in a proper way. This study describes the activities done by teachers in five kindergartens in Indramayu. The participants in this study were five teachers in those five kindergartens. The findings showed that the teachers in five kindergartens in Indramayu taught vocabulary by presenting some activities such as; listen and do, listen and repeat, modeling and demonstration, singing song, look and say, listen and identify, and question and answer. In Grade A the dominant activity was Listen and Repeat with frequency 40% in one semester while in Grade B, Look and say was the dominant activity with frequency 30,76% in one semester. Those activities are done based on the consideration that the activities done in Grade A were emphasized on their level of development such as imitating. While children in Grade B were more developed, the activities were emphasized on recognizing word and learn to pronounce it clearly.